Hot Student Stories
top-5-grammar-and-spelling-checkers-to-rock-in-2019

Using the completing-the-square method, rewrite f(x) = x2 + 4x − 1 in vertex form.

Mindee Nelson

in Mathematics

follow
followin
1 answer
5 views

1 answer


Whitney Matthews on March 17, 2018

Answerf(x) = (x + 2)2 - 5Explanation f(x) = x2 + 4x − 1 is y = f(x) y = x2 + 4x − 1 y + 1 = x2 + 4xMake the right-hand side of the equation a perfect square by adding (b/2)2 to both sides. and + 1 + (4/2)2 = x2 + 4x + (4/2)2y + 1 + 4 = x2 + 4x + 22 + 5 = (x + 2)2Subtracting 5 on both sides.and + 5 - 5 = (x + 2)2 - 5y = (x + 2)2 - 5now replace y with f(x)f(x) = (x + 2)2 - 5


Add you answer